Towards Managing Library Competencies and Strategic Analysis "SWOT" to Achieve Competitive Advantage: Strategic Human Resources Management in Main Libraries for Public Reading as an Example - djaidja, billal; sidhoum, khalida (Journal of Social Sciences and Humanities, 2021)
Public libraries are primarily institutions of learning, with the task of collecting intellectual resources and providing services to meet the needs of the community of information, they serve as a gateway to knowledge and learning for life, so they must have a human resource to achieve these lofty and future goals. The human resource, which must be highly efficient and professional, allows it to perform its functions and the activities of the library and its operations and services vary from all categories of society, regardless of its types or educational and intellectual levels, healthy or disabled. Human resources are important factors in the success of public libraries, so they need to manage the affairs of the workers and ensure that their professional and formative needs are met, the human resources management is the process of taking care of all the individuals that the public library needs to achieve its objectives, This process includes attracting these resources, supervising their use, maintaining, maintaining, guiding and developing them, in accordance with a strategy that ensures the integration and balance between achieving the objectives of the library and the objectives of its employees. The inclusion of the human resource in the strategic decisions of public libraries has become a necessity to ensure the continuation of its mission, to preserve its human resources, to achieve professionalism and high efficiency at the long-term level, and to create a competitive environment with its external environment, and this can only be achieved through the role provided by the administration. The strategy for human resources and making it a competitive factor that public libraries seek to employ in order to provide outstanding services compared to other libraries.